Factors Associated with Postoperative Complications Following Resection of Sinonasal Tumors: A NSQIP Analysis - Raymond J. So; Hannan A. Qureshi; Evelyn M. Leland; Anirudh Saraswathula; Murugappan Ramanathan; Nyall R. London; Nicholas R. Rowan (Sinusitis)
Background: As the surgical repertoire for the management of sinonasal tumors evolves over time, an improved understanding of risks for postoperative complications is imperative. Objectives: To identify factors associated with 30-day postoperative complications following the resection of sinonasal tumors. Methods: The National Surgical Quality Improvement Program (NSQIP) database was queried from 2005 to 2020 for patients undergoing open or endoscopic surgical resection of sinonasal tumors. A Cox proportional hazards model was used to identify factors associated with postoperative complications. Kaplan–Meier survival analyses and log-rank tests were used to compare time to complication onset. Frailty was defined as a 5-factor modified frailty index score > 2. Results: Of the 859 patients with sinonasal tumors, 539 (62.7%) were male, and the average age (± SD) was 59.3 ± 14.1 years. Postoperative complications were observed in 251 (29.2%) patients. The most common 30-day complications were bleeding requiring transfusions (n = 172; 20.0%) and ventilation longer than 48 h (n = 37; 4.3%). Frailty (aHR [95% CI]: 3.58 [1.80–7.12]), malignancy (3.43 [1.59–7.38]), and maxillary tumor location (2.40 [1.86–3.09]) were associated with greater risk for 30-day postoperative complications. Similarly, patients with frailty (χ2 = 7.0; p = 0.008), malignant tumors (χ2 = 13.4; p < 0.001), or maxillary sinus tumors (χ2 = 34.6; p < 0.001) experienced earlier onset of postoperative complications. Conclusions: Frailty, malignancy status, and tumor location may modulate risk for 30-day postoperative complications following the resection of sinonasal tumors. These results may help to inform preoperative patient counseling and identify individuals at increased risk of postoperative complications.